Education that Fosters Environmental Literacy - Forsyth, Deborah (My University, 2018)
This study was conducted to examine the effects of exploratory play in nature combined with locally based, environmental education (EE), on the environmental literacy (EL) of students in a lower elementary Montessori classroom. The study included one lower elementary Montessori classroom consisting of 24 students of which there were 12 girls and 12 boys, ranging from six to nine years of age. Activities consisted of environmental games, environmental art, lessons and activities that were designed to develop knowledge of the flora and fauna in and around the school. Lessons were followed with opportunities to write/draw reflections on lesson content or complete additional research. Data included questionnaires completed by students before and after the study, parent surveys, student interviews, teacher observations, and samples of student work. Though there were limitations of cold weather and time period, data demonstrated an increase in environmental literacy during the course of the study.
Research Paper, M..S.E., Montessori, UWRF, 2018.
Keywords: Montessori; environmental literacy; environmental education